2016
DOI: 10.3109/15376516.2016.1139024
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to bisphenol A (BPA) in Wistar rats reduces sperm quality with disruption of ERK signal pathway

Abstract: Bisphenol A (BPA) is an estrogenic environmental toxin widely used in the production of plastics and ubiquitous human exposure to this chemical has been proposed to be a potential risk to human health. Exposure to BPA can negatively impact sperm quality. However, the mechanism remains largely unknown. The objectives of this study were to assess the role of BPA on sperm quality and explore the possible mechanisms. The Wistar male rats (aged 28 days) were administered BPA by oral gavage for 28 days at dose of 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Thus, its continuous exposure and its ubiquitous presence in the environment have raised public health concerns (Bergman, Heindel, Jobling, Kidd, & Zoeller, ). Population‐based (Meeker et al., (); Li et al., () and animal‐based studies have reported male reproductive abnormalities resulting from BPA exposure such as state of hypogonadotropic hypogonadism (Wisniewski et al., (), adverse effects on morphology, growth and sexual development (Lam et al., ) and also endocrine and reproductive dysfunctioning (Milla, Depiereux, & Kestemont, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, its continuous exposure and its ubiquitous presence in the environment have raised public health concerns (Bergman, Heindel, Jobling, Kidd, & Zoeller, ). Population‐based (Meeker et al., (); Li et al., () and animal‐based studies have reported male reproductive abnormalities resulting from BPA exposure such as state of hypogonadotropic hypogonadism (Wisniewski et al., (), adverse effects on morphology, growth and sexual development (Lam et al., ) and also endocrine and reproductive dysfunctioning (Milla, Depiereux, & Kestemont, ).…”
Section: Introductionmentioning
confidence: 99%
“…As an EDC, BPA has the potential to work as a weak estrogen receptor α/β (ERα/β) agonist 18 and to alter hormonal signal through binding to ERs on male germ cells. So, BPA related devastating effects such as low spermatozoa count 19 , sperm protein alteration 20 , toxicity development in spermatozoa via DNA damage 21 , DNA methylation 22 and oxidative stress 23 have been studied well. Moreover, studies like BPA induced disruption in meiotic progression during spermatogenesis 24 and reduction in chromosome crossover 25 have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Different functional and morphological disorders have been reported on the testicular tissue following the in vivo exposure to nanoparticles (Asare et al, ; Komatsu et al, ). Inducing the oxidative stress by generating the reactive oxygen species (ROS) and free radicals (Zhang et al, ), suppression of spermatogenesis (Wisniewski et al, ) and alteration of testicular enzyme activity and hormones are the prevalent effects of nanoparticles on testis (Li et al, ). The histopathological investigation showed that administration of ZnO‐NPs affects the spermatids and spermatocyte quality as well as the testicular cell wall and seminiferous tubules disrupted at the higher concentration in a dose‐dependent manner (Figure a–d).…”
Section: Discussionmentioning
confidence: 99%